The Effects of Exposure to Social Media Content on Body Image Disturbance in Post-Pandemic Adolescents - Samsidar, Samsidar (PT. Anagata Sembagi Education, 2025)
Post-COVID-19 pandemic, social media usage has increased significantly, especially among adolescents. This trend coincides with the increasing pressure on beauty standards disseminated through social media content such as Instagram, TikTok, and YouTube. This study aims to explore how exposure to social media content affects adolescents’ body image disorders after the pandemic. Using a qualitative approach through in-depth interviews with ten adolescent girls aged 15-18 years, this study found that most respondents experienced dissatisfaction with their bodies after consuming content that displayed ideal beauty standards. Pressure to appear perfect, social comparison, and social media algorithms that amplify exposure to similar content are the main triggers for the emergence of body image disorders. This study highlights the need for stronger digital literacy and psychological education to help adolescents develop a healthy relationship with their bodies.